Perancangan User Interface Pura Teluk Terima Dengan Metode Design Thinking - I Nyoman Tri Anindia Putra; Anak Agung Dewi Puspita Sari; Nyoman Trinity Laksmi Maharani (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
Bali is renowned as a tourist destination with its natural beauty and religious traditions, earning it the nickname "Island of a Thousand Temples." In this era, the dissemination of information related to Bali's holy temples has become increasingly difficult to find and confirm its authenticity. Therefore, by focusing on the research object of the "Pura Teluk Terima" and incorporating the development of the digital era, as well as addressing the issues faced by prospective visitors by involving several respondent samples, a design thinking method was implemented to design an information system. The outcome of this design is a prototype that allows visitors to gain a deeper understanding of the Pura Teluk Terima. Once the information system was ready for testing, it underwent usability testing using the System Usability Scale method, achieving an excellent score of 82.8125 with a grade of B